Strategy to Build Defense Industry Competitiveness in Welcoming Golden Indonesia 2045 - Wihyawari, Sailenius Amelion; Sudiarso, Aries; Jandhana, I B Putra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This journal discusses the strategies needed to build the competitiveness of the Indonesian defense industry to meet the target of Indonesia Emas 2045. The defense industry is an important aspect in achieving this goal as Indonesia faces various security and stability challenges. Through an in-depth review of the factors affecting the competitiveness of the defense industry, this study presents several key strategies that can be implemented to improve the potential and performance of the Indonesian defense industry. These strategies include technology optimization, collaboration among stakeholders, human resource development, increasing production capabilities, and meeting international standards. The research hopes to provide guidance for stakeholders in facing global and regional challenges to ensure Indonesia's defense industry becomes strong and competitive by 2045.